Investigating University EFL Teachers’ Perception, Practice, and Challenges in Self-Initiated Professional Development - Mitiku Garedew Tessema; Girma Gezahegn Belihu (Journal of Languages and Language Teaching, 2023)
The topic of self-initiated professional development has garnered increasing attention among English as a Foreign Language (EFL) teachers who are motivated to identify and address gaps in their professional development. This study aimed to investigate the perceptions, practices, and challenges of EFL teachers at Addis Ababa Science and Technology University with regard to self-initiated professional development. The participants consisted of 35 EFL instructors with 12 holding PhD degrees and the remaining 23 holding MA degrees at Addis Ababa Science and Technology University. The study adopted a concurrent mixed methods research design, utilizing both a questionnaire and semi-structured interviews for data collection. The study employed a total population sampling method and conducted semi-structured interviews with four randomly selected EFL teachers. Data analysis was performed separately for the questionnaire and interview data, followed by a mixed analysis to triangulate and corroborate the results. The findings revealed that the majority of the EFL teachers had a positive perception of self-initiated professional development, which was reflected in their practice of self-monitoring and analyzing critical incidents. However, the teachers did not engage in practices such as keeping a teaching journal, conducting action research, reflecting on their teaching, or developing a teaching portfolio. The challenges to self-initiated professional development were identified as lack of commitment, collaboration among colleagues, communication, and institutional support. This study highlights the potential of self-initiated professional development as an alternative means of addressing professional development needs among EFL teachers.